PERSEPSI PEMUSTAKA TERHADAP LAYANAN MINANGKABAU CORNER DI PERPUSTAKAAN UNIVERSITAS ANDALAS - Rifan Irfandi; Ardoni Ardoni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
This study aims to determine how the user's perception of the Minangkabau Corner service at the Andalas University Library. Minangkabau Corner's service is to develop Minang culture and advance Andalas University in making Minangkabau Corner a center that includes Minang culture itself. Meanwhile, according to Febrin Anas Ismail, the purpose and function of the Minangkabau Cornerini service itself is to disseminate information on Minang culture in printed/digital form, one of which is shown to Minang people who are wandering. It can be concluded that the Minangkabau Cornerini service itself has the purpose and function of the Minangkabau Cornerini service itself to preserve Minang cultural collections, whether in printed or digital form, as well as treat ancient manuscripts. The factors that influence a person's perception are as follows: a. Stereotypes, namely views about the behavioral characteristics of a particular group of people. For example ethnic groups, religion, economic class, gender, ethnicity and others. b. Self-perception, namely the view of oneself that can affect the formation of first impressions. Various studies show a tendency to see the similarities that exist between oneself and with new people. c. Situations and groups, namely the view of someone who is influenced by certain situations and conditions. d. Characteristics that exist in other people, namely a person's physical attractiveness that can cause special judgments when first met. This research is a quantitative research, data collection techniques using a questionnaire. The population is 30,583 Andalas University students, while the sample is 99 respondents. The results showed that most of the users answered that they were happy with the services of the Minangkabau Corner, both in terms of librarians or the Minangkabau Corner itself.